Quantifying the incidence of clinically significant respiratory depression in women with and without obesity class III receiving neuraxial morphine for post-cesarean analgesia: a retrospective cohort study. (August 2021) - Ende, H.B.; Dwan, R.L.; Freundlich, R.E.; Dumas, S.; Sorabella, L.L.; Raymond, B.L.; Lozada, M.J.; Shotwell, M.S.; Wanderer, J.P.; Bauchat, J.R.
Highlights: Incidence of respiratory depression post-cesarean after neuraxial morphine. Guidelines recommend increased monitoring of obesity class III patients. Incidence of respiratory depression in non-obese 9.4/10 000 (95% CI 3.7 to 24.3). Incidence in obesity class III 25.7/10 000 (95% CI 11.0 to 60.0). Study was underpowered to identify a risk difference (OR 2.2, 95% CI 0.6 to 6.9). Abstract: Background: Obesity is a suspected risk factor for respiratory depression following neuraxial morphine for post-cesarean analgesia, however monitoring guidelines for obese obstetric patients are based on small, limited studies. We tested the hypothesis that clinically significant respiratory depression following neuraxial morphine occurs more commonly in women with body mass index (BMI) ≥40 kg/m 2 compared with BMI <40 kg/m 2 . Methods: We conducted a single-center, retrospective chart review (2006–2017) of obstetric patients with clinically significant respiratory depression following neuraxial morphine, defined as: (1) opioid antagonist administration; (2) rapid response team activation (initiated in April 2010); or (3) tracheal intubation due to a respiratory event. The incidence of respiratory depression was compared between women with BMI ≥40 kg/m 2 and BMI <40 kg/m 2 . Results: In total, 11 327 women received neuraxial morphine (n=1945 BMI ≥40 kg/m 2 ; n=9382 BMI <40 kg/m 2 ). Women with BMI ≥40 kg/m 2 had higher rates of sleep apnea, hypertensive disorders, and magnesium administration. Sixteen cases of clinically significant respiratory depression occurred within seven days postpartum. The incidence did not significantly differ between groups (odds ratio 2.2, 95% CI 0.6 to 6.9, P =0.174). Neuraxial morphine was not deemed causative in any case, however women with BMI ≥40 kg/m 2 had higher rates of tracheal intubation unrelated to neuraxial morphine (2/1945 vs. 0/9382, P =0.029). Conclusions: Respiratory depression in this population is rare. A larger sample (∼75 000) is required to determine whether the incidence is higher with BMI ≥40 kg/m 2 . Tracheal intubation was higher among the BMI ≥40 kg/m 2 cohort, likely due to more comorbidities.